The Correlation between Physical Rehabilitation Compliance and Muscle Strength in Post-Stroke Patients with Hemiplegia - Serin Izzatut Taqiyah; Dian Hudiyawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Post-stroke patients will experience weakness, paralysis, or disability as a result of the stroke attack, thus requiring rehabilitation. The rehabilitation results will be more optimal if supported by the compliance of post-stroke patients in following the rehabilitation program. The purpose of this study was to determine the correlation between physical rehabilitation compliance and muscle strength in post-stroke patients with hemiplegia. The type of research used in this study is using a cross-sectional analytic approach. The study population was post-stroke patients undergoing physical rehabilitation at Ir. Soekarno Sukoharjo Hospital with an average of 73 patients using the Slovin formula. The inclusion criteria in this study were patients who performed physical rehabilitation regularly for 1 month, and patients willing to become respondents in the study by signing a consent form. Exclusion criteria in this study were patients who suddenly re-entered the inpatient clinic, patients who had repeated stroke attacks, and patients who suddenly moved to hospital locations. Collection of rehabilitation compliance data according to the rehabilitation compliance questionnaire. Collection of muscle strength data by existing muscle strength measurements. The results of the Spearman Rho correlation obtained a significance value (p-value) of 0.001 (p<0.05), the majority of respondents were in the age range of 60-74 years, most of the respondents were male, most of the respondents were married, most had undergone rehabilitation for 3 months, and the majority were first stroke patients. This study concludes that there is a correlation between physical rehabilitation compliance and muscle strength of post-stroke patients with hemiplegia at Ir. Soekarno Sukoharjo Hospital.